Cardiometabolic and immune factors associated with increased common carotid artery intima-media thickness and cardiovascular disease in patients with systemic lupus erythematosus - Ammirati, E.; Bozzolo, E.; Contri, R.; Baragetti, A.; Palini, A.; Cianflone, D.; Banfi, M.; Uboldi, P.; Bottoni, G.; Scotti, I.; Pirillo, A.; Grigore, L.; et al. (Elsevier, 2014)
Background and aim: Patients with systemic lupus erythematosus (SLE) have a higher prevalence of subclinical atherosclerosis and higher risk of cardiovascular (CV) events compared to the general population. The relative contribution of CV-, immune- and disease-related risk factors to accelerated atherogenesis in SLE is unclear. Methods and results: Fifty SLE patients with long-lasting disease (mean age 44±10 years, 86% female) and 50 sex- and age-matched control subjects were studied. Common carotid artery intima-media thickness (CCA-IMT) was used as a surrogate marker of atherosclerosis. We evaluated traditional and immune- and disease-related factors, assessed multiple T-cell subsets by 10-parameter-eight-colour polychromatic flow cytometry and addressed the effect of pharmacological therapies on CCA-IMT. In SLE patients, among several cardiometabolic risk factors, only high-density lipoprotein levels (HDL) and their adenosine triphosphate-binding cassette transporter 1 (ABCA-1)-dependent cholesterol efflux capacity were markedly reduced (p < 0.01), whereas the CCA-IMT was significantly increased (p=0.03) compared to controls. CCA-IMT correlated with systolic blood pressure, low-density lipoprotein (LDL) cholesterol and body mass index (BMI), but not with disease activity and duration. The activated CD4 + HLA-DR + and CCR5 + T-cell subsets were expanded in SLE patients. Patients under hydroxychloroquine (HCQ) therapy showed lower CCA-IMT (0.62±0.08 vs. 0.68±0.10mm; p=0.03) and better risk-factor profile and presented reduced circulating pro-atherogenic effector memory T-cell subsets and a parallel increased percentage of naïve T-cell subsets. Conclusion: HDL represents the main metabolic parameter altered in SLE patients. The increased CCA-IMT in SLE patients may represent the net result of a process in which 'classic' CV risk factors give a continuous contribution, together with immunological factors (CD4 + HLA-DR + T cells) which, on the contrary, could contribute through flares of activity of various degrees over time. Patients under HCQ therapy present a modified metabolic profile, a reduced T-cell activation associated with decreased subclinical atherosclerosis. © 2014 Elsevier B.V.